FORMATION OF INDICATORS THE PROCESSES OF PREHEATING AND HEATING AFTER THE VEHICULAR ENGINE START BY USING COMPLEX HEATING SYSTEM WITH PHASE-TRANSITIONAL THERMAL ACCUMULATOR - Volkov, V.; Grytsuk, I.; Волков, В. П.; Грицук, И. В.; Грицук, І. В. (Харьковский национальный автомобильно-дорожный университет, 2016)
The article deals with the features of applying a vehicular engine complex heating system with phase-transitional thermal accumulator. The results of experimental studies of heating the vehic-ular engine are shown. Using a phase-transitional thermal accumulator in the engine coolant heater system allows to considerably reduce the time for heating.
ФОРМИРОВАНИЕ ПОКАЗАТЕЛЕЙ ПРОЦЕССОВ ПРЕДПУСКОВОГО И ПОСЛЕПУСКОВОГО ПРОГРЕВА АВТОМОБИЛЬНОГО ДВИГАТЕЛЯ С КОМПЛЕКСНОЙ СИСТЕМОЙ ПРОГРЕВА С ТЕПЛОВЫМ АККУМУЛЯТОРОМ ФАЗОВОГО ПЕРЕХОДА
ФОРМУВАННЯ ПОКАЗНИКІВ ПРОЦЕСІВ ПЕРЕДПУСКОВОГО ТА ПІСЛЯПУСКОВОГО ПРОГРІВУ АВТОМОБІЛЬНОГО ДВИГУНА З КОМПЛЕКСНОЮ СИСТЕМОЮ ПРОГРІВУ З ТЕПЛОВИМ АКУМУЛЯТОРОМ ФАЗОВОГО ПЕРЕХОДУ
Keywords: complex heating; vehicular engine; pre-start and after-start heating; heating processes; vehicle; комплексный прогрев; транспортный двигатель; предпусковой и послепусковой прогрев; режимы прогрева; транспортное средство; комплексний прогрів; транспортний двигун; передпусковий і післяпусковий прогрів; режими прогріву; транспортний засіб; 621.43+621.43.016.4-57+536.421+541.6:541.183